2007
DOI: 10.1182/blood-2007-01-069781
|View full text |Cite
|
Sign up to set email alerts
|

CTLA-4 polymorphisms and clinical outcome after allogeneic stem cell transplantation from HLA-identical sibling donors.

Abstract: CTLA-4 is an inhibitory molecule that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
85
4
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(106 citation statements)
references
References 37 publications
15
85
4
1
Order By: Relevance
“…It has been reported that the CT60 A allele is associated with a higher level of the sCTLA-4 mRNA than the CT60 G allele. 17,28 These results indicate that the À318 C allele and the CT60 A allele contribute to the reduction in CTLA-4 inhibitory function and to T-cell activation. However, association of the þ 49 A allele with a higher expression of CTLA-4 and augmentation of CTLA-4 inhibitory function has been reported.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…It has been reported that the CT60 A allele is associated with a higher level of the sCTLA-4 mRNA than the CT60 G allele. 17,28 These results indicate that the À318 C allele and the CT60 A allele contribute to the reduction in CTLA-4 inhibitory function and to T-cell activation. However, association of the þ 49 A allele with a higher expression of CTLA-4 and augmentation of CTLA-4 inhibitory function has been reported.…”
Section: Discussionmentioning
confidence: 79%
“…However, it might be because of our small cohort, as Perez-Garcia et al 17 demonstrated that the donor CT60 AA genotype was associated with an increased risk of grade II-IV acute GVHD in a large cohort of 536 donors. All of the patients in our study were Japanese, and many of them (75%) had received BM as a stem-cell graft.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations